Dr. Jared P. Kirtland, Cleveland’s First Malacologist and Some of His Correspondence - Ralph W. Dexter (Hello World!, 1977)
This paper is based upon a report given at the 40th Annual Meeting of the American Malacological Union held at the Springfield Mlseum of Science, Springfield, Mass., on 6 August 1974.